Oslovski kašelj - epidemiološke značilnosti in preprečevanje - Sočan, Maja (Zdravstveno varstvo, 2003)
In the prevaccine era, virtually every child used to get whooping cough causedby Bordetella pertussis. Vaccination or naturally occurring illness doesnot assure lifelong immunity. Waning immunity in adolescents and adults causes the susceptibility to pertussis but the clinical picture is mild and uncharacteristic. This part of the population represents the reservoir for nonimmunised infants. There is a possibility to vaccinate adults with acellular pertussis vaccine and lower the transmission to small children. The results of the studies using acellular vaccine in adults are promising - regarding the good immune response and low rate of adverse reactions. Before making the recommendation for adult pertussis vaccination programme there are many questions to be answered. The pertussis epidemiology must be monitored intensively.
Keywords: epidemiologija; oslovski kašelj; preventiva